Development of diagnostic tools for IBDV detection using plants as bioreactors - Gomez, Evangelina Raquel; Cassani, María Florencia; Lucero, Maria Soledad; Parreño, Viviana; Chimeno Zoth, Silvina Andrea; Berinstein, Analia (SpringerOpen, 2020)
Infectious bursal disease virus (IBDV) is the etiological agent of an immunosuppressive and highly contagious disease that affects young birds, thus causing important economic losses in the poultry industry. Multimeric particles with different architectures based on the capsid protein VP2 have been widely produced for different purposes. We hereby show the production and easy recovery of IBDV subviral particles (SVP) from transiently transformed Nicotiana benthamiana. The SVP, which were observed by electronic microscopy, proved to be antigenically and immunogenically similar to the virion. Indeed, anti-IBDV antibodies from samples of infected birds recognized these SVP and, when injected intramuscularly, these subviral particles also evoked a humoral immune response in chickens. We developed an in-house ELISA using SVP as coating reagent that demonstrated to be highly accurate and in good agreement with a commercial ELISA. This study demonstrates that the recombinant antigen generated and the technology used to produce it are suitable for developing a diagnostic tool against Infectious bursal disease.